Phrarātchabanyat khāt̨ōpth̄æn phūslahāi læ khāthotth̄æn læ khāchaičhāi læ čhaaml̄œi nai khadī āyā Ph̨̄o. S̨̄o. 2544 - Thiraphon Arunakasil̨ō (Winyūchon, 2002)
The 2001 law on compensation to the accused in the Thai criminal court.